PENGARUH TEH HIJAU DALAM MENURUNKAN TEKANAN DARAH: SYSTEMATIC REVIEW - La Ode Alifariki; Adius Kusnan (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2022)
The condition of the systolic blood pressure greater than 140 mmHg And when the diastolic blood pressure is greater than 90 mmHg is a condition of hypertension in which the causative component is not can be recognized, referred to as secondary, due to suffering from certain diseases. Green tea contains polyphenols and L-theanine which can decrease the neurotransmitter serotonin, thus blood pressure in the arteries is believed to decrease because of these components. This study aims to review articles on the effects of green tea in lowering blood pressure. This research is limited from 2000 to 2022 and gets 5 eligible articles sourced from the Google Scholar search engine with the keywords “green tea, blood pressure AND hypertension. The results of the study reported that from 5 articles it was found that green tea was effective in lowering blood pressure in patients with hypertension.